Excess iodide-induced reactive oxygen species elicit iodide efflux via β-tubulin-associated ClC-3 in thyrocytes. Issue 5 (4th March 2022) - Yu, Meisheng; Wei, Yuan; Wang, Pengyuan; Deng, Zhiqin; Mao, Jianwen; Zhu, Linyan; Chen, Lixin; Peng, Shuang; Wang, Liwei
Abstract : Iodide (I − ) is crucial to thyroid function, and its regulation in thyrocytes involves ion transporters and reactive oxygen species (ROS). However, the extent of 2Cl − /H + exchanger (ClC-3) involvement in the iodide (I − ) efflux from thyrocytes remains unclear. Therefore, we examined the effects of ClC-3 on I − efflux. ClC-3 expression was found to significantly alter the serum TT3 and TT4 concentrations in mice. We further found that excess I − stimulation affected ClC-3 expression, distribution, and I − efflux in FRTL-5 cells. Immunofluorescence analyses indicated that ClC-3 mainly accumulated in the cell membrane and co-localized with β-tubulins after 24 h of excess I − treatment, and that this process depended on ROS production. Thus, ClC-3 may be involved in I − efflux at the apical pole of thyrocytes via excess I − -induced ROS production and β-tubulin polymerization. Our results reveal novel insights into the role of ClC-3 in I − transport and thyroid function.